Ethnogenesis of the Bafut Ethnic Group: A Frontier Process - Ngengwe, Perpetua (Technium Social Sciences Journal, 2025)
This paper explores the ethnogenesis of the Bafut ethnic group, of the Western Grassfield of Cameroon, as an analytic case study. The objective of the study is to attain a deeper understanding of ethnogenesis as a frontier process, by applying the Internal Frontier Thesis, developed by Igor Kopytoff. The study investigates how through processes consistent with the Internal Frontier thesis, the Bafut ethnic group characterized by shared, centralized, hierarchical hereditary organization, could have developed from diverse settlement patterns. Ethnographic fieldwork consisting of participant observation, in-depth interviews and various data collection techniques, made it possible for the researcher to access implicit cultural structures from an emic perspective. The fieldwork was conducted as part of the KPAAMCAM (Key Pluridisciplinary Advances on African Multilingualism, Cameroon) project, provided qualitative data, for analyzing how distinct lineages with autonomous origins, could come together into a unified ethnic group. The findings suggests that this is the result of incorporation, kinship redefinition and shared political institutions. This paper contributes to the understanding of internal frontiers as crucibles of ethnogenesis and state formation, while also offering insights into the continuity of indigenous socio-political systems in contemporary context. It also challenges the static model of ethnicity, highlighting the role of sociopolitical and ritual processes, in governing identity formation.